2020
DOI: 10.3389/fpsyg.2020.00841
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies and Self-Efficacy in University Students: A Person-Centered Approach

Abstract: In daily academic life, students are exposed to a wide range of potentially stressful situations which could negatively affect their academic achievement and their health. Among the factors that could be weakened by academic stress, attention has been paid to expectations of self-efficacy, which are considered one of the most important determinants for student engagement, persistence, and academic success. From a proactive perspective, research on academic stress has emphasized the importance of coping strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
93
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(147 citation statements)
references
References 90 publications
5
93
0
2
Order By: Relevance
“…In the case of the association between resilience and coping strategies , the results showed that resilience is associated with a greater number of coping strategies –positive association with problem-focused strategies and negative with emotion-focused– especially in the case of perceived control, acceptance of change and perceived competence . These results expand on and refine those found in prior evidence ( 84 , 91 98 ), since the three behavioral factors would make the use of emotional management strategies less necessary; a higher level of self-regulation allows situations to be perceived with a lower level of stress ( 1 , 10 , 83 87 , 89 , 90 , 93 100 , 104 , 105 , 113 – 116 , 122 125 , 143 145 , 148 ). It is noteworthy that the stress tolerance factor (stress) was less related to emotion-focused strategies, which also implies a lower level of perceived stress ( 101 103 ).…”
Section: Discussionsupporting
confidence: 83%
“…In the case of the association between resilience and coping strategies , the results showed that resilience is associated with a greater number of coping strategies –positive association with problem-focused strategies and negative with emotion-focused– especially in the case of perceived control, acceptance of change and perceived competence . These results expand on and refine those found in prior evidence ( 84 , 91 98 ), since the three behavioral factors would make the use of emotional management strategies less necessary; a higher level of self-regulation allows situations to be perceived with a lower level of stress ( 1 , 10 , 83 87 , 89 , 90 , 93 100 , 104 , 105 , 113 – 116 , 122 125 , 143 145 , 148 ). It is noteworthy that the stress tolerance factor (stress) was less related to emotion-focused strategies, which also implies a lower level of perceived stress ( 101 103 ).…”
Section: Discussionsupporting
confidence: 83%
“…Further, under non-pandemic conditions peer support, social support ( 58 , 59 ) and self-efficacy ( 60 ) are next to other factors crucial for general well-being, life satisfaction, and also academic performance ( 60 62 ) especially in University students. Due to the lockdown measures and social distancing, especially the peer and social support (rather than family support) dropped out, which can explain the present results.…”
Section: Discussionmentioning
confidence: 99%
“…Este dato, así pues, es consistente con los estudios que, desde un enfoque centrado en la variable, encontraron una relación positiva entre estrategias aproximativas de afrontamiento y fortalezas personales (Freire et al, 2019;Gustems-Carnicer y Calderón, 2016). Asimismo, la relación entre flexibilidad en el afrontamiento y fortalezas personales evidenciada en este trabajo se suma a la incipiente línea de trabajos que vinculan la disponibilidad de recursos psicológicos personales con la capacidad del estudiantado universitario para conjugar de forma adaptativa distintas estrategias frente al estrés (e.g., Freire et al, 2020).…”
Section: Discussionunclassified
“…Esta incipiente línea de investigaciones abre la puerta al estudio de los recursos psicológicos personales que contribuyen a que los estudiantes más flexibles en su afrontamiento del estrés logren estados de salud mental más adaptativos. En este sentido, Freire et al, (2020) han evidenciado recientemente que la flexibilidad en el afrontamiento se relaciona positivamente con las expectativas de autoeficacia del estudiantado universitario.…”
Section: Introductionunclassified